Zfp423 Promotes Adipogenic Differentiation of Bovine Stromal Vascular Cells - Huang, Yan; Das, Arun Kr; Yang, Qi-Yuan; Zhu, Mei-Jun; Du, Min (PLOS ONE, 2012)
Intramuscular fat or marbling is critical for the palatability of beef. In mice, very recent studies show that adipocytes and fibroblasts share a common pool of progenitor cells, with Zinc finger protein 423 (Zfp423) as a key initiator of adipogenic differentiation. To evaluate the role of Zfp423 in intramuscular adipogenesis and marbling in beef cattle, we sampled beef muscle for separation of stromal vascular cells. These cells were immortalized with pCI neo-hEST2 and individual clones were selected by G418. A total of 288 clones (3×96 well plates) were isolated and induced to adipogenesis. The presence of adipocytes was assessed by Oil-Red-O staining. Three clones with high and low adipogenic potential respectively were selected for further analyses. In addition, fibro/adipogenic progenitor cells were selected using a surface marker, platelet derived growth factor receptor (PDGFR) α. The expression of Zfp423 was much higher (307.4±61.9%, P<0.05) in high adipogenic cells, while transforming growth factor (TGF)-β was higher (156.1±48.7%, P<0.05) in low adipogenic cells. Following adipogenic differentiation, the expression of peroxisome proliferator-activated receptor γ (PPARγ) and CCAAT/enhancer binding protein α (C/EBPα) were much higher (239.4±84.1% and 310.7±138.4%, respectively, P<0.05) in high adipogenic cells. Over-expression of Zfp423 in stromal vascular cells and cloned low adipogenic cells dramatically increased their adipogenic differentiation, accompanied with the inhibition of TGF-β expression. Zfp423 knockdown by shRNA in high adipogenic cells largely prevented their adipogenic differentiation. The differential regulation of Zfp423 and TGF-β between low and high adipogenic cells is associated with the DNA methylation in their promoters. In conclusion, data show that Zfp423 is a critical regulator of adipogenesis in stromal vascular cells of bovine muscle, and Zfp423 may provide a molecular target for enhancing intramuscular adipogenesis and marbling in beef cattle.